Asthma in women : implications for pregnancy and perinatal outcomes - Tata, Laila J. (2007)
Background: Asthma now affects up to 10% of pregnant women in high income countries and international prevalence is rising. It is already one of the commonest chronic diseases that can complicate pregnancy and previous studies have raised concern that women with asthma have increased pregnancy risks. Precise estimates of the magnitude of these risks and the extent to which they may differ by asthma severity and asthma exacerbation rates, have not been determined.